LITERATURE REVIEW: EFEKTIVITAS PEMBERIAN AROMATERAPI LAVENDER SECARA INHALASI DAN MASASE TERHADAP PENURUNAN NYERI PERSALINAN KALA I - Nilot Mahesi; Lilik Indahwati; Ratna Diana Fransiska (STIKes Maharani Malang, 2023)
Labor pain is soreness and discomfort due to uterine contractions and cervical dilatation. Pain can affect the mother's condition during childbirth if the mother's perception of pain is very bad, so it causing anxiety and stress. Therefore, pain management is needed to prevent disturbances during labor. Lavender aromatherapy is a non-pharmacological pain management method to treat labor pain. The use of lavender aromatherapy for pain management is often applied by inhalation and massage. The Aims of this research is to determine the differences in the effectiveness of lavender aromatherapy by inhalation and massage to reduce the first stage of the labor pain during. The Design of this research is literature review that using 10 research articles published in reputable journals. The Result are lavender aromatherapy can reduce the labor pain from severe to moderate pain and lavender aromatherapy massage can make labor pain intensity during the first stage of the active phase remains at a moderate level. Giving lavender aromatherapy by inhalation is more effective in reducing labor pain intensity than massage because it provides a faster effect and shorter interventions. The health workers can take advantage of lavender aromatherapy with inhalation and massage methods to redure labour pain. Keywords: lavender aromatherapy, inhalation, massage, pain labor.